Crystal structure of the co-crystalline adduct 1,3,6,8-tetraazatricyclo[4.4.1.13,8]dodecane (TATD)–4-iodophenol (1/2): supramolecular assembly mediated by halogen and hydrogen bonding - Augusto Rivera; Jicli José Rojas; Jaime Ríos-Motta; Michael Bolte (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The asymmetric unit of the title co-crystalline adduct, 1,3,6,8-tetraazatricyclo[4.4.1.13,8]dodecane (TATD)–4-iodophenol (1/2), C8H16N4·2C6H5IO, comprises a half molecule of the aminal cage polyamine plus a 4-iodophenol molecule. A twofold rotation axis generates the other half of the adduct. The components are linked by two intermolecular O—H...N hydrogen bonds. The adducts are further linked into a three-dimensional framework structure by a combination of N...I halogen bonds and weak non-conventional C—H...O and C—H...I hydrogen bonds.